Implementation of Islamic religious learning strategies in children with autism in Indonesia - Cahyo Adi Kistoro, Hanif; Kartowagiran, Badrun; Latipah, Eva; Naim, Ngainun; Putranta, Himawan (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Important religious education is given to children with autism. Objective. This research aims to analyze teachers’ experience in implementing Islamic religious learning strategies (IRLS) for children with autism. Methods. This research is qualitative research with a phenomenological approach. The participants were six Islamic religion teachers from two exceptional schools in Yogyakarta who were selected using a purposive sampling technique. In-depth interviews and observation methods were used in data collection techniques. The coding analysis method, with the stages of data organization, reading data, coding data, determining and connecting themes with descriptions, and interpreting data, was used for data analysis. Results. The research results found that IRLS for children with autism has three stages, namely planning, implementation, and evaluation. Planning is done to determine the preparation that must be done before the learning process. Learning implementation includes reading and writing as well as interpreting the material. The evaluation is carried out to determine the level of success of the learning process that has been carried out. The IRLS carried out by teachers include two-way communication, adequate experience, and innovation skills. Conclusion. The strategies are expected to be further enhanced to reduce constraints in learning.